Injury incidence among student-athletes when combining academic studies and elite sports in Sweden - A prospective cohort study - Tervo, T.; Tengman, E.; Mårs, T.; Flatholm, E. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Sports injuries are a widespread concern among collegiate athletes (1), sometimes leading to unexpected ends to athletic careers. Various models of dual career systems have been introduced for combining elite sports and academic studies, acknowledging the need for alternative pathways (2). However, managing dual careers can be demanding for students, particularly in the initial academic year due to elevated pressure and low academic function (3). The purpose of the present study was to examine the injury incidence among student-athletes during the first year of studying as well as to identify risk factors for injury in this population. METHODS: Two surveys were employed, one year apart, between 2018 and 2022 at a University in Sweden. Two-hundred and forty-three student-athletes (101 men, 142 women, mean age: 22,1 [18-36]) responded to a baseline survey in conjunction with their first semester of study. The one-year follow-up survey was answered by 111 student-athletes (47 men, 64 women, mean age: 22,9 [19-37]). The survey addressed the sports student`s injury occasions, injury characteristics, sports participated in, experienced stress, recovery methods, management of leisure time and study pace. Independent samples t-test, chi-square test, univariate and multivariate regression were used in the analysis. RESULTS: Fifty-one percent of the students reported having sustained an injury on some occasion the year before study start. Moreover, during the one-year follow-up, 54% of the students reported an injury during the first year of studying. The students reporting an injury prior to study start were more likely to sustain a new injury during the first year of studying (OR=3.174, p=>0.01). Sex, type of sport participated in, psychological stress, study pace, relaxation management, and leisure time management were not associated with an increased injury risk in this population. CONCLUSION: Findings from the present study indicates that injury one year prior to study start aggravates injury risk during the first year of studies for these student-athletes. Experienced stress was not found as an injury predictor in this population which may emphasizes the importance of having a supportive environment around the student-athletes, however, more research is needed to investigate this further. Considering the high prevalence of injury incidence found in this study, developing preventive methods is key.